2018
DOI: 10.1039/c8nj00778k
|View full text |Cite
|
Sign up to set email alerts
|

New ionic liquids based on systemic acquired resistance inducers combined with the phytotoxicity reducing cholinium cation

Abstract: Systemic acquired resistance (SAR) is one of the most promising ways to support plants in the fight against viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…A broad range of pathogens, including numerous organisms like viruses, bacteria, nematodes, insects, fungi etc., can be resisted by non-pathogens through a process called induced systemic resistance (ISR) ( Jain et al, 2013 ; Ryu et al, 2005 ; Wu et al, 2018 ). Apparently the systemic acquired resistance is almost identical to ISR characterized by the motivation through an incompatible pathogen ( Kukawka et al, 2018 ). An extensively studied demonstrated that plant growth-promoting rhizobacteria (PGPR) consists a useful association with the plant root and the rhizosphere ( Kloeppe et al, 1999 ; Ma et al, 2018 ).…”
mentioning
confidence: 99%
“…A broad range of pathogens, including numerous organisms like viruses, bacteria, nematodes, insects, fungi etc., can be resisted by non-pathogens through a process called induced systemic resistance (ISR) ( Jain et al, 2013 ; Ryu et al, 2005 ; Wu et al, 2018 ). Apparently the systemic acquired resistance is almost identical to ISR characterized by the motivation through an incompatible pathogen ( Kukawka et al, 2018 ). An extensively studied demonstrated that plant growth-promoting rhizobacteria (PGPR) consists a useful association with the plant root and the rhizosphere ( Kloeppe et al, 1999 ; Ma et al, 2018 ).…”
mentioning
confidence: 99%
“…The same plant immune inducer can be paired with surfactant-type cation for better wetting or tetrabutylammonium cation for faster dissolution. Using this strategy, 15 immunity inducers including SA, BTH, INA, BABA, etc., were paired with the cholinium cation to form ionic liquids ( Kukawka et al, 2018 ). Their abilities to induce SAR were tested using the tobacco-TMV pathosystem.…”
Section: Emerging Trendsmentioning
confidence: 99%
“…While bifunctional combination approaches have shown the potential to either improve the efficacy or reduce phytotoxicity, the introduction of the second chemical moiety has also brought more complications. For example, Pip, a SAR mobile signal candidate, showed significantly reduced SAR-inducing activity when paired with cholinium ( Kukawka et al, 2018 ). On the other hand, while isonicotinate did not induce SAR, its cholinium ionic liquid was shown to induce SAR ( Kukawka et al, 2018 ).…”
Section: Emerging Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…[29] In our recent work, we reported that spraying application of nicotinic acid to tobacco plants enhances its resistance to pathogens. [30] Moreover, isonicotinic acid when transformed into the salt form became even more biologically active which resulted in 45 % diminution of quantity of necrotic spots caused by virial infection in tested model system. The main goal of this article is to examine new derivatives of isonicotinic and 2,6dichloroisonicotinic acids and find the correlation between the modification in chemical structure of amide functional group of the elicitor and its impact on biological efficiency in inducing plant resistance against pathogens.…”
Section: Introductionmentioning
confidence: 97%